(untitled) (Asian Journal of Social Science Studies, 2022)
Finance is the bloodline of the real economy, serving the real economy is the vocation of finance, is the purpose of finance, is also one of the important tools to improve the quality of the development of the real economy, how to make finance better serve the development of the real economy is the main line of research in this paper. This paper takes the current situation of the development of financial services for the real economy in the Dalian Free Trade Zone as the starting point, analyzes the problems of the financial services system in the Free Trade Zone in depth, and proposes corresponding strategies to improve the financial services system from financial services, financial technology and green finance, so that the financial services in the Free Trade Zone can better serve the high-quality development of the real economy.